Prediction of Student Scholarship Recipients Using the K-Means Algorithm and C4.5 - Wandri, Rizky; Arta, Yudhi; Hanafiah, Anggi; Oktaviaani, Rizka (AI Society & STMIK Indonesia, 2023)
The government has a program called